Comparison of image quality and radiation dose between prospectively ECG-triggered and retrospectively ECG-gated CT angiography: Establishing heart rate cut-off values in first-generation dual-source CT - Ünal, Emre (Anatol J Cardiol, 2015)
OBJECTIVE: To evaluate radiation dose and image quality of prospectively electrocardiography (ECG)-triggered and retrospectively ECG-gated coronary computed tomography (CT) angiography and to establish cut-off values of heart rates (HRs) for each technique in firstgeneration dual-source CT. METHODS: A total of 200 consecutive patients with suspected coronary artery disease were accepted into the study. Patients were selected randomly for each technique (prospective triggering group n=99, mean age 55.85±10.74 and retrospective gating group n=101, mean age 53.38±11.58). Two independent radiologists scored coronary artery segments for image quality using a 5-point scale. Also, attenuation values of each coronary artery segment and dose-length product values were measured. For each technique, cut-off HR values were determined for the best image quality. RESULTS: Mean image quality scores and attenuation values were found to be higher in the prospective triggering group (p<0.05). Mean radiation dose was 73% lower for the prospective triggering group (p<0.01). The cut-off HR values for good image quality scores were ≤67 beats per minute (bpm) and ≤80 bpm for the prospective triggering and retrospective gating groups, respectively (p<0.05). Increased HR (≥68 and ≥81 bpm, respectively) had negative effects on image quality (p<0.05). CONCLUSION: The prospective ECG triggering technique has better image quality scores than retrospective ECG gating, particularly in patients who have an HR of less than 68 bpm. Also, a 73% radiation dose reduction can be achieved with prospective ECG triggering. In patients with higher heart rates, retrospective ECG gating is recommended.